2013
DOI: 10.1007/bf03405667
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Montreal Heat Response Plan During the 2010 Heat Wave

Abstract: xtreme heat episodes result in significant morbidity, especially in northern latitudes or areas influenced by more temperate climates. 1,2 A recent meta-analysis showed that both environmental factors, such as the absence of air conditioning, and population risk factors, such as having cardiovascular or psychiatric co-morbidities, increase the probability of heat-related deaths. 3 Following the European heat wave of 2003, 15,000 excess deaths were reported in 12 European countries during the first week of Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…We also did not distinguish actions undertaken > 30°C. Moreover, the Montreal HAP has been revised and updated yearly since 2007 (Price et al 2013); this was not specifically considered in the present study. Further research could consider how incremental changes in policies affected mortality reduction, if at all.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also did not distinguish actions undertaken > 30°C. Moreover, the Montreal HAP has been revised and updated yearly since 2007 (Price et al 2013); this was not specifically considered in the present study. Further research could consider how incremental changes in policies affected mortality reduction, if at all.…”
Section: Discussionmentioning
confidence: 99%
“…The European heat wave of 2003 prompted the Montreal Public Health Department (PHD) to develop a HAP to reduce heat-related mortality and morbidity (Price et al 2013). Implemented in 2004, the HAP comprises a spectrum of interventions triggered at different alert levels based on temperature forecasts of Environment Canada.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, however, it would be ideal if we could test and refine this approach in a context where other, more conventional epidemiologic methods have been used to identify excess deaths. For example, Price et al identified 106 of the 304 deaths as being heat-related via chart review after the 2010 event in Montreal [25]. Alternatively, the methods could be optimized using simulated data, in which the excess and expected deaths have been clearly defined.…”
Section: Discussionmentioning
confidence: 99%